(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2026)
Exposure to caustic agents like sulfuric acid and rodenticides remains a major public health concern. While individual ingestion of either agent is well-documented, simultaneous intake is exceptionally rare and poses a heightened risk of rapid systemic toxicity and gastrointestinal devastation. We report a fatal case involving simultaneous ingestion of sulfuric acid. The patient showed severe corrosion and necrosis of the lips and perioral area, while the esophagus remained intact, reflecting the known resistance of esophageal squamous epithelium to acid damage. The stomach exhibited extensive coagulative necrosis without perforation, likely due to the presence of approximately 80 ml of semi-digested food that may have lessened tissue injury. Corrosive damage extended to the larynx and upper trachea, causing inflammation and epiglottic swelling. These findings indicate aspiration of acid-contaminated gastric contents, leading to aspiration pneumonia, a major cause of death alongside potential laryngeal edema and respiratory arrest. This case highlights the grave morbidity and mortality risk from accidental combined ingestion of corrosive and toxic agents. It stresses the urgent need for public education on safe storage and handling of hazardous chemicals.